Hypophosphataemia after parathyroidectomy in chronic renal failure. Issue 6319 (20th March 1982) - Farrington, K; Varghese, Z; Baillod, R A; Fernando, O N; Moorhead, J F
Abstract : Out of 24 patients receiving haemodialysis who were subjected to parathyroidectomy, 13 developed hypophosphataemia; this persisted for 3-52 weeks (mean 10.6 weeks). Before operation these 13 patients had had significantly higher plasma alkaline phosphatase activities (p less than 0.01) and significantly higher values in iliac crest bone biopsy samples for active resorption surface and active formation surface (p less than 0.05 in each case) than the group who remained normophosphataemic. Significantly more of the patients who remained normophosphataemic had shown periarticular calcification in preoperative skeletal radiographs (p less than 0.001). Hypophosphataemia may result from reduced mobilisation of phosphate from bone or its increased accretion into bone, and resorption of phosphate from periarticular mineral deposits may protect against development.